1982
DOI: 10.1007/bf01064761
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for long-term care: Comments from board-and-care residents

Abstract: In these times of shrinking human services resources, establishing clear service priorities becomes all the more necessary. This is particularly true for the care of chronically mentally ill persons, whose many needs place high service demands on the care system. As a group these patients rarely have a say in the establishment of service priorities. To obtain a better idea of their perceived needs, we asked 278 randomly selected, mentally disabled residents in 30 Los Angeles board-and-care homes about their cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
2
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
1
9
2
2
Order By: Relevance
“…It remains to be seen if the same phenomenon occurs when part of a naturally occurring quality-improvement effort. Studies conducted in other health care settings and populations have shown that open-ended questions yield information that is different from and more specific than that produced by closed-ended questions in terms of desired improvements in care quality (Billings & Kolton, 1999;Chesney, Lindeke, Johnson, Jukkala, & Lynch, 2005;Lehman, Reed, & Possidente, 1982). Unlike these previous studies, the results from the current study indicate a reliable method for coding open-ended responses that quantifies the scope of open-ended comments into two types of improvement (staff care processes and resident outcomes).…”
Section: Discussioncontrasting
confidence: 47%
“…It remains to be seen if the same phenomenon occurs when part of a naturally occurring quality-improvement effort. Studies conducted in other health care settings and populations have shown that open-ended questions yield information that is different from and more specific than that produced by closed-ended questions in terms of desired improvements in care quality (Billings & Kolton, 1999;Chesney, Lindeke, Johnson, Jukkala, & Lynch, 2005;Lehman, Reed, & Possidente, 1982). Unlike these previous studies, the results from the current study indicate a reliable method for coding open-ended responses that quantifies the scope of open-ended comments into two types of improvement (staff care processes and resident outcomes).…”
Section: Discussioncontrasting
confidence: 47%
“…On pose ensuite des questions ouvertes quant aux occasions récentes de plaisir et de contrariété, aux préoccu-pations actuelles et aux aspirations. Ces questions sont aussi reprises de deux enquêtes américaines récentes (Lehman et al, 1982;Spivack étf 0/., 1982) auprès de patients psychiatriques chroniques dans la communauté. Ces enquêtes fournissent ainsi des points de repères pour la lecture des données qué-bécoises.…”
Section: Le Programme Espoirunclassified
“…Gregory [36] found a significant relationship between satisfaction and meaning of activities, as defined by the concept of personal causation, value, and interests mentioned in the Model of Human Occupation (Kielhofner, 2002). Lehman [37] identified four factors related to global well-being: satisfaction with health, leisure, social relationships, and financial situation.…”
Section: Introductionmentioning
confidence: 99%